Centering multilingual learners and countering raciolinguistic ideologies in teacher education principles, policies and practices - Bale, Jeff; Gagné, Antoinette; Brubacher, Katie 1976-; Burton, Jennifer 1983-; Kerekes, Julie 1965-; Larson, Elizabeth Jean 1981-; Nii, Mama Adobea Owoo 1987-; Rajendram, Shakina 1987-; Wong, Wales 1981-; Zhang, Yiran 1990- (Language, education and diversity, 2023)
"This book details a study of teacher education programs that prepare teachers to work with multilingual learners. The book examines how racism and linguicism shape the conditions under which teacher candidates learn how to teach, and offers guiding principles and a suite of teacher education practices to disrupt the interplay of language and race"--